Environmental pollution and child health in central and Eastern Europe. - Fitzgerald, E F (1998)
For the last 50 years, the economic and industrial development of the nations of Central and Eastern Europe has been achieved at the cost of environmental degradation. The health risks posed by this pollution to children and the steps necessary to ameliorate such risks are only beginning to be investigated. At a recent conference in Poland, sponsored in part by the National Institute of Environmental Health Sciences, participants from 11 countries in the region, together with scientists from Western Europe and the United States, met to share information regarding pediatric environmental health in Central and Eastern Europe, to consider methodologic issues in the design and conduct of such studies, and to discuss preventive strategies. This report summarizes the deliberations, outlines problem areas such as heavy metals and air pollution, delineates research and training needs to help Central and Eastern Europeans deal more effectively with such problems, and recommends specific future actions and collaborative efforts.